Mediation in museums and exhibitions: learning about art and its system - Grinspum, Denise (2014)
The text presents a reflection on the learning contexts in art museums and discusses the didactical resources suitable for the development of aesthetic understanding. It also proposes the understanding of the art system for the intelligibility of the contemporary artistic production, highlighting the difficulties in defining parameters for its learning.